A Bibliometric Analysis of Turkey's Contribution to Bone Health Literature from an Endocrinologist Perspective - YAVUZ, DİLEK (TURKIYE KLINIKLERI, 2019)
Objective: To analyze the trend of Turkish publications related to bone health with respect to global publications and to determine the relative contribution of endocrinologists to metabolic bone disease literature. Material and Methods: Publications related to bone health up to and including the year 2017 were retrieved from the Web of Science (WoS) and TUrkiye Atif Dizini (TAD) database using metabolic bone disease related MeSH terms. Excel (v15.30) and Endnote X8 were used to summarize the bibliometric features, including the number of publications, authors, their affiliations, and contributing countries. Keywords were divided, for a detailed analysis, into three clusters: osteoporosis, parathyroid, and vitamin D-related. Results: A total of 1.880.666 papers were retrieved from WoS globally and, of those, 21.165 (1.13%) were published from Turkey. Of the papers published from Turkey, 3.0% were primarily contributed by endocrinologists. The relative contribution of endocrinology to osteoporosis-related (4.6% vs. 1.5%), parathyroid-related (23.7% vs. 5.3%), and vitamin D-related (23.7% vs. 5.3%) publications was higher for articles originating from Turkey compared to the global data. Endocrinology was among the top five specialties contributing to Turkish metabolic bone disease literature indexed in WoS and TAD. Conclusion: Turkey has a less than expected rate of research output in terms of metabolic bone disease. The relatively higher contribution of endocrinology to that effort is promising. Supporting bone research might accelerate the efforts of Turkish researchers in the field of metabolic bone health.
Keywords: Metabolic bone disease; bibliometric analysis; Turkey; endocrinology; osteoporosis